Relationship Between Hand-washing Habit and Toilet Use with Diarrhea Incidence in Children Under Five Years - Nikmatur Rohmah; Fariani Syahrul (Universitas Airlangga, 2017)
Diarrhea is still a public health problem in the world and the mostly occur in children under five years. At the moment the number of diarrhea-caused mortality was 3.8 per 1000 per year by 3.2 episodes per year in children under five years. This research aims to analyze the association between hand-washing habits and toilet use with the incidence of diarrhea in children under five years. This is an observational analytic with cross sectional study. Population of the research was a children's mother took her children to the public health center of Sekardangan Sidoarjo Subdistrict. The number of samples taken as many as 58 mother of children under five years. Data collection was done with interviews to parents of children and the observations of the toilets. Technique of data analysis using chi-square test or Fisher's exact test. On the results of the research there is a significant association the habit of hand washing (p = 0.006) and toilet use(p = 0.014) with the incidenceof diarrhea in children under five years. Conclusions of the research is the habit of hand washing and toilet use had a significant association with the incidenceof diarrhea in children under five years. Advice that can be given to the mother of a children under five years is to wash the hands before and after defecating and before preparing food for children.   Keywords: diarrhea, hand washing, toilet use, observational, children under five years